2015
DOI: 10.2139/ssrn.2657673
|View full text |Cite
|
Sign up to set email alerts
|

Regulating Employment Relationships in the Sharing Economy

Abstract: to-lhc-sharing-eco/> (using "sharing economy," "peer economy," and "collaborative consumption"). The "sharing economy" has come under increasing fire, both for its ostensible inaccuracy (it's really not about sharing) and for its unhclpfulncss (if it's not about sharing, then what is it about?).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
11
0
1
Order By: Relevance
“…In this study, we have shown that in Helsinki, the rise of digital short-term rental platforms is especially pronounced in Kallio, Kamppi and Punavuori, old working-class districts with a liberal atmosphere and trendy urban culture. The public discourse has portrayed the rise of digital tourism services as a seemingly technical question related to the attractiveness and fairness of Finland's business environment; and until now, the City of Helsinki has adopted a "wait-and-see" (Acevedo, 2016) attitude towards the growing popularity of Airbnb and other digital short-term rental platforms. At the same time, the city has actively promoted a culture that has emphasized deregulation in the form of "the removal of unnecessary obstacles that hinder encounters and actions with impact" with the purpose of encouraging value production through individual (entrepreneurial) activity, as well as the promotion of authenticity and lively urban culture (Jokela, 2019;Kuudes Kerros & City of Helsinki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we have shown that in Helsinki, the rise of digital short-term rental platforms is especially pronounced in Kallio, Kamppi and Punavuori, old working-class districts with a liberal atmosphere and trendy urban culture. The public discourse has portrayed the rise of digital tourism services as a seemingly technical question related to the attractiveness and fairness of Finland's business environment; and until now, the City of Helsinki has adopted a "wait-and-see" (Acevedo, 2016) attitude towards the growing popularity of Airbnb and other digital short-term rental platforms. At the same time, the city has actively promoted a culture that has emphasized deregulation in the form of "the removal of unnecessary obstacles that hinder encounters and actions with impact" with the purpose of encouraging value production through individual (entrepreneurial) activity, as well as the promotion of authenticity and lively urban culture (Jokela, 2019;Kuudes Kerros & City of Helsinki, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…And thus, this brings us back to Acevedo's (2016) comments about the wait-and-see approach to regulation. It relies on the assumption that more precise regulatory intervention is possible, but only once the market has become somewhat settled.…”
Section: Regulatory Responses To Sharing Economy Successmentioning
confidence: 93%
“…On the other hand, enthusiasts of creating a consistent regulation claim that this is the only way of amending emerging market errors that users alone are not able to overcome (Codagnone and Martens, 2016). Because of the dynamic development of cooperation economy and difficult direction of development, there appear voices are inducing to refrain from choosing the appropriate way and wait for an appropriate moment (Acevedo, 2016).…”
Section: Literature Review On Sharing Economymentioning
confidence: 99%